QUIPPER SCHOOL: HOW DO TEACHERS BRING IT IN THE CLASSROOM? - Asep Idin; M. Syahrul Z. Romadhoni (International Conference on Education and Language (ICEL), 2016)
The advanced development of internet has influenced mankind in almost all aspects of life including the field of English Language Teaching (ELT). In response to it, English teachers should make use of it to enhance the quality of their teaching. One of its strategies is by using Quipper School, a popular educational online platform focusing on helping teachers and students dealing with internet use in the teaching learning. Quipper School contains a smart management tool that helps them get involved in teaching learning in more interactive ways. It also provides an assessment program that enables teachers to evaluate and monitor the students’ progress. Most students feel excited and amazed as they experience a new mode of English learning. Quipper School was introduced in Indonesia in 2013, and now gains its fast popularity. This paper strives to explain theoretical bases of teaching English with ICT, the nature of Quipper School, basic features of Quipper School, sample of teaching materials, some teaching procedures in designing and using Quipper School for the teaching of English focusing on reading skill, and the reflection.